P142 Results of the 3rd interim analysis of C-Patrol: a non-interventional study on olaparib in german routine clinical practice. (1st November 2019) - Marmé, F; Hilpert, F; Welslau, M; Grabowski, JP; Seitz, J; El-Balat, A; Hartkopf, AD; Glowik, R; Sehouli, J
Abstract : Introduction/Background: Olaparib (50 mg hard capsules, HC) was the 1st PARPi approved in the EU in 12/2014 as monotherapy for maintenance treatment of adult patients with platinum-sensitive relapsed BRCA -mutated ( BRCA m) ovarian cancer (PSR-OC) who are in response to platinum-based chemotherapy. In addition, film-coated tablets (FT, 100/150 mg) were approved in 05/2018 regardless of BRCA status. Here, we report for the first time data on real-world olaparib treatment from patients who switched from HC to FT. Methodology: The German prospective non-interventional study C-PATROL (NCT02503436 ) collects routine clinical and patient-reported outcome data in BRCA m PSR-OC patients treated according to label with olaparib with the recommended total daily dose of 800 mg (HC) or 600 mg (FT). The 3rd interim analysis (cut-off: 01APR2019) for patients treated with olaparib (HC/FT) reflects data on patient characteristics and safety by using descriptive statistics focussing on 'switcher' (here patients can be treated with FT since 08/2018). Results: 252 olaparib-treated patients were analysed; 177 (70.2%) were treated with HC, 47 (18.7%) switched from HC to FT, and 28 (11.1%) were newly initiated with FT. Median therapy durations for the three subgroups were 9.0 months (HC), 17.4 months (switcher; 13.4 months before [HC] and 4.4 months after [FT] switch) and 9.2 months (FT). 44 switcher (93.6%) had adverse events (AEs); 41 (87.2%) before and 26 (55.3%) after switching. Treatment modifications due to AEs were more frequent prior to switching (i.e. during HC treatment). In total, 30 switcher had therapy modifications; 25 (83.3%) before and 11 (36.7%) after switching. Conclusion: The 3rd interim analysis indicates that under routine conditions, olaparib is well tolerated in patients who switched from HC to FT. In fact, fewer AEs occurred after switching. The toxicity profile observed so far is in line with the results of the clinical trial program for olaparib in PSR-OC and 1st-line maintenance. Funding: AstraZeneca. Disclosure: F. Marmé: honoraria received for speaker, consultancy or advisory role, travel, from AstraZeneca, Tesaro, Roche, Novartis, Pfizer, PharmaMar, GenomicHealth, CureVac, Amgen, Eisai, MSD, Celgene, Clovis. F. Hilpert: membership on advisory boards for AstraZeneca, Roche, Tesaro, Clovis, MSD, PharmaMar, receipt of honoraria from Astra Zeneca, Clovis, Roche, Tesaro, MSD, PharmaMar, Pfizer, Novartis. M. Welslau: No conflict of interest, nothing to disclose. J. P. Grabowski: Advisory, consultancy and speakers activities for AstraZeneca, Tesaro, Clovis, Riemser, honoraria from AstraZeneca, Tesaro, Roche, Clovis, Pfizer, Riemser. J. Seitz: no conflict of interest, nothing to disclose. A. El-Balat: membership on advisory councils, speaker's activities for AstraZeneca, Roche, PharmaMar, Olympus. A. D. Hartkopf has received honoraria (speakers bureau and consulting fees) from AstraZeneca, Eisai, GenomicHealth, Lilly, MSD, Novartis, Pfizer, Roche, Tesaro, Teva. R. Glowik: employee of AstraZeneca. J. Sehouli: Advisory and expert activities for PharmaMar, Clovis, Tesaro, Roche, Roche Diagnostics, Astra Zeneca, Merck, Bayer, Eisei, Johnson and Johnson, MSD, Novocure, Amgen, Lilly; Receipt of professional fees from PharmaMar, Clovis, Tesaro, Roche, Astra Zeneca, receipt of research grant support (institution) from PharmaMar, Clovis, Tesaro, Roche, Astra Zeneca, Medimmune, Bristol Myers, Lilly.